2018
DOI: 10.1002/ejlt.201700347
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Liposomes Containing Natural and Synthetic Lipids Formed by Microfluidic Mixing

Abstract: Vesicle formation by a staggered herringbone microfluidic mixer is investigated in comparison to a sonication‐extrusion method. Experiments focused on the incorporation efficiency of lipid components, on dye entrapment efficiency, and on the barrier properties of the vesicle bilayers produced. The microfluidic method produces vesicles largely under the control of thermodynamic factors. As a result, the molecular parameters of the lipids (chain length, chain volume, head group area) directly control vesicle dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Despite the high demands for sterically stabilised drug delivery systems, most existing microfluidics studies (not limited to SHM) reported the production of non-PEGylated formulations (Forbes et al, 2019;Guimarães Sá Correia et al, 2017;Kastner et al, 2015;Maeki et al, 2015;Zhigaltsev et al, 2012). Few studies reported the preparation of PEGylated liposomes, which were either very small in size (~50 nm), unstable or of high dispersity (> 0.2) (Dong et al, 2017;Hood et al, 2014;Ran et al, 2016;Zheng and Fyles, 2018;Zhigaltsev et al, 2015;Zizzari et al, 2017). For instance, Zhigaltsev et al failed to produce stable and monodispersed, high phase-transition liposomes (DPPC or HSPC) using SHM microfluidics, and mixing with unsaturated lipids was needed to enhance the stability of these PEGylated liposomes (Zhigaltsev et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the high demands for sterically stabilised drug delivery systems, most existing microfluidics studies (not limited to SHM) reported the production of non-PEGylated formulations (Forbes et al, 2019;Guimarães Sá Correia et al, 2017;Kastner et al, 2015;Maeki et al, 2015;Zhigaltsev et al, 2012). Few studies reported the preparation of PEGylated liposomes, which were either very small in size (~50 nm), unstable or of high dispersity (> 0.2) (Dong et al, 2017;Hood et al, 2014;Ran et al, 2016;Zheng and Fyles, 2018;Zhigaltsev et al, 2015;Zizzari et al, 2017). For instance, Zhigaltsev et al failed to produce stable and monodispersed, high phase-transition liposomes (DPPC or HSPC) using SHM microfluidics, and mixing with unsaturated lipids was needed to enhance the stability of these PEGylated liposomes (Zhigaltsev et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Different microfluidic approaches have been developed for making liposomes, including the HFF method, microfluidic jetting technique, [ 63 ] droplet emulsion transfer, [ 64 ] electroformation, [ 65 ] NanoAssemblr (Figure 4b), [ 58,66–68 ] tangential flow filtration device, [ 69 ] and other microfluidic devices. [ 70,71 ] Among these methods, the HFF method is a straightforward method that has been widely used to synthesize nanoliposomes with various compositions and functions.…”
Section: Microfluidic Synthesis Of Organic Npsmentioning
confidence: 99%
“…[61] Also, drug-loaded liposomes produced using microfluidic methods exhibited higher EE, smaller and more uniform size in comparison with those synthesized using the conventional thin-film hydration method. [62] Different microfluidic approaches have been developed for making liposomes, including the HFF method, microfluidic jetting technique, [63] droplet emulsion transfer, [64] electroformation, [65] NanoAssemblr (Figure 4b), [58,[66][67][68] tangential flow filtration device, [69] and other microfluidic devices. [70,71] Among Reproduced with permission.…”
Section: Liposomesmentioning
confidence: 99%